Challenges and limitations for the systematic collection of cycling data from bike sensors - Costa, Miguel (2020)
Information and Communication Technology is increasingly recognised as a key element for the ability of cycling mobility initiatives to create real, profound, incremental and measurable impact. Even though previous work has extensively explored many applications of smart cycling data, the first challenge is to actually produce consistent cycling data in a systematic way. In this research, we explore the range of sensors which could be more relevant to integrate into urban bicycles to support the systematic collection of data about cycle routes. To gain a deeper insight into the real-world challenges of systematic cycle-based sensing, we conducted an experimental data collection. We equipped a bicycle with a diverse set of low-cost sensors, and we collected data in a pre-defined route, in which it was possible to experience very diverse environmental circumstances regarding road surface or the level of surrounding traffic. The results highlight some of the practical challenges that can be faced by systematic sensing for urban cycling, suggesting that not all sensors might be appropriate for this type of large-scale deployment on bicycles. The main contribution is a set of design implications, which should help to inform the design of novel sensing systems for bicycles.